Silver Screen, Sacred Story: Using Multimedia in Worship - Bausch, Michael G. (Rowman & Littlefield Publishers, 2002)
Our culture has undergone a major shift: younger generations have less and less interest in the printed word as they become predominantly image oriented. In response, as congregations increasingly learn to be more sophisticated in using newer electronic technologies, they are finding themselves at different places in the quest to understand, acquire, manage, and benefit from the technology boom. Worship leaders in congregations already using some electronic media are realizing that they could be doing more with it, and are seeking new ideas. Congregational leaders scrambling to catch up with a worship committee that has decided it's time for a change aren't sure of the next steps. Or maybe there's been a gift to the congregation to be spent on electronics, and no one is quite sure how best to use the money. Michael Bausch's book grows out of several years' of conversation, personal experimentation, and experience with multimedia worship in one modest-sized, small-town church, while also drawing on the experiences and work of other churches learning to use electronic media in worship. Bausch balances concern for practical issues, such as finances and architecture, with attention to theological integrity and the challenges of sustaining media-enhanced worship. He skillfully shows how the artistic resources of the world around us can enhance our awareness of God's presence in worship.